Food security in rural Burkina Faso: The importance of consumption of own-farm sourced food versus purchased food - Fraval, Simon; Yameogo, Viviane; Ayantunde, Augustine A.; Hammond, James; Boer, Imke J.M. de; Oosting, Simon J.; Wijk, Mark T. van (Springer, 2020)
The number of undernourished people and the risk of micro-nutrient deficiency remain high in sub-Saharan Africa (SSA). Decades of policy designed to reverse the trends of food insecurity have illustrated that the causal pathways of intervention to end-point outcomes, such as nutrition, are not necessarily straightforward. Utilising proxies for dimensions of food security, this study investigates the relative importance of different pathways to food security in two subtly contrasting communities in the Sahelian and Sudanian Savanna zones of Burkina Faso.In Yatenga province, approximately 31% of households were classified as ‘severely food insecure’ in the ‘lean’ period. In contrast, over 84% of households sampled in Seno province were classified as being ‘severely food insecure’ in the ‘lean’ period. There were statistically significant associations between food security indicators and off-farm income, farm income and production diversity. The source of income had significantly different associations with diet diversity in the two provinces. In Yatenga province, higher gross farm income in the absence of off-farm income was predicted to result in more diverse diets; in Seno province, however, gross farm income was only predicted to result in more diverse diets when households are also earning off-farm income.Our analysis shows that households were most differentiated by income generating pathways to food security in the ‘lean’ period. This finding should not detract from the essential role played by home-produced foods in improving food security. Rather, market-orientated agriculture and production for home consumption, as shown by households in this study, can be combined as part of a more resilient livelihood strategy. Policy needs to be targeted towards agro-ecological conditions, as well as socioeconomic factors in order to facilitate improved on-farm income, farm resilience and off-farm employment opportunities.